ORGANIZED ECOLABELLING: NORTH-SOUTH IMPLEMENTATION OF “KICKING AWAY THE LADDER” (CASE: PALM OIL TRADE BETWEEN INDONESIA AND EUROPE) - Nanda Kartika Ayu (Review of International Relations, 2020)
Liberalization is one of the theis that is expected to be able to answer the acceleration and development of the economy of developing countries. One element of liberalization is market openness that will make developing countries unite with global markets both in accepting investments or trading in exports and imports. However, along with the development of technology, the demand for the North (developed countries) in carrying out its trade began to implement an "ecolabelling" policy. For developing countries with all their industrial capabilities, ecolabelling policy is the same as the non-tarrif limitation policy given by developed countries to developing countries. So that this paper will focus on the application of the ecolabelling policy provided by the North to products that will enter the northern market, as one of the efforts of the northern countries to apply "kicking away the ladder", assuming the Southern state does not get a balanced trade surplus with the north and continues to be a developing country. This writing will use a structuralist approach that concentrates on the international structure of the north and south to describe the relationship between developed and developing countries, and uses the concept of "kicking away the ladder" to answer the situation from the implementation of ecolabelling policies for South countries. The author uses qualitative studies using literature review sources through books, journals and online media. Keywords: Ecolabelling, Kicking away the ladder.  North-South relations